Characterisation of heterogeneous microstructure in large forged products using nonlinear ultrasonic method. Issue 6 (12th April 2020) - Abraham, Saju T.; Shivaprasad, S.; Das, C.R.; Albert, S. K.; Venkatraman, B.; Balasubramaniam, Krishnan
ABSTRACT: A comparative study between the ultrasonic attenuation and the nonlinearity is presented for the characterisation of microstructure in large dimension forgings. Results are provided for two austenitic stainless steel forgings of AISI type 304L with a diameter 200 mm, where microscopic observations reveal abnormal grain growth near the surface of one of the forgings. Frequency dependence of the nonlinearity parameter is used to discern variations in grain size in these forgings more precisely than attenuation measurements. The distribution of grain size is shown to have a significant influence on the nonlinearity parameter. Relative changes in the nonlinearity parameter with applied frequency were correlative with the microstructural variations in both the forgings.